Simulation and Designing of Network Signal Booster at 900 MHz - Jain, Saksham; Saini, Vikrant; Chauhan, Brajlata (International Journal of Computer Sciences and Engineering, 2020)
The primary aim of this paper is to present simulation findings and design network signal booster at a frequency of 900 MHz RF. The booster is designed to work on GSM system bandwidth. The gain given by the amplifier circuit was 12dB at the middle frequency with a difference of +-1.3 dB to normalize. The monopole antennas used for signal reception and transmission that have 0.9141-1315i input impedance and -18.18dB return loss. The study includes detailed graphical and tabular view of the results at each design level, simulation.